2007
DOI: 10.1002/cjoc.200790090
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities, Densities and Refractive Indices of Rubidium Chloride or Cesium Chloride in Ethanol Aqueous Solutions at Different Temperatures

Abstract: The data of solubilities, densities and refractive indices of rubidium chloride or cesium chloride in the system C 2 H 5 OH-H 2 O were measured by using a simple accurate analytical method at different temperatures, with mass fractions of ethanol in the range of 0 to 1.0. In all cases, the presence of ethanol significantly reduced the solubility of rubidium chloride and cesium chloride in aqueous solution. The solubilities of the saturated solutions were fitted via polynomial equations as a function of the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
1
13
1
1
Order By: Relevance
“…The solubilities, densities, and refractive indices for DMA (1) + NaCl/KCl/RbCl/CsCl (2) + H 2 O (3) systems at 298.15 K, 308.15 K, and 318.15 K are given in Table and Figures to . For comparison, the solubilities of NaCl, KCl, RbCl, and CsCl in pure water at 298.15 K are listed in Table S2, which are in good agreement with the literature values. , …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The solubilities, densities, and refractive indices for DMA (1) + NaCl/KCl/RbCl/CsCl (2) + H 2 O (3) systems at 298.15 K, 308.15 K, and 318.15 K are given in Table and Figures to . For comparison, the solubilities of NaCl, KCl, RbCl, and CsCl in pure water at 298.15 K are listed in Table S2, which are in good agreement with the literature values. , …”
Section: Resultssupporting
confidence: 81%
“…16,17 Secondary amides S2, which are in good agreement with the literature values. 19,20 In Figure 3, it can be observed that the solubility decreased by increasing the ratio of DMA to water in the solvent. The effect of the temperature is that higher temperatures increase the solubility.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, the addition of ILs to the aqueous solution of inorganic salts may cause the salting-out effect and can be employed in crystallization for producing supersaturation in a solution. In the past decade, our group has focused on the phase behavior of the ternary or quaternary systems consisting of the heavy alkaline metal (Rb, Cs) salts and organic solvent–water mixtures , to evaluate the application of the salting-out effect in increasing the yield of expensive Rb and Cs salts. As a continuation of our series work, we reported herein the solubility, density, and refractive index of RbCl/CsCl + ILs + H 2 O ternary solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our group focused on the study of phase behavior of monohydric alcohol + rubidium or cesium salts + water ternary systems at different temperatures to investigate the salting effect of monohydric alcohol, such as ethanol, 1-propanol, or 2-propanol. , To extend our work, the polyhydric alcohol is chosen instead of monohydric alcohol in this work. Herein, we report the solubility, refractive index, density, and viscosity for the ternary systems polyhydric alcohol + CsBr + H 2 O at various temperatures.…”
Section: Introductionmentioning
confidence: 99%